REDUCTION OF GLUCOSINOLATES CONTENT DURING SAYUR ASIN FERMENTATION [Penurunan Kandungan Berbagai Glukosinolat selama Fermentasi Sayur Asin] - Probo Y. Nugrahedi; Caesariana A. Priatko; Matthijs Dekker; Budi Widianarko; Ruud Verkerk (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
Glucosinolates (GLSs), health promoting compounds commonly found in Brassica vegetables, were studied during sayur asin fermentation made from Indian mustard (B. juncea). The current preliminary study aims to investigate the changes of glucosinolates content during 3 and 7 days of fermentation in two different media, i.e. coconut water and tajin liquor, and salt concentrations of 2.5 and 10%. The glucosinolates were analysed by HPLC after sample extraction in hot methanol followed by purification and de-sulphation. Results show that sinigrin was the most dominant glucosinolate among others, i.e. gluconapin, glucobrassicin, 4-hydroxy-glucobrassicin, 4-methoxy-glucobrassicin, and neo glucobrassicin, accounting for about 1000 and 4000 µmol/10 g dw in raw Indian mustard. Unfortunately, fermentation has substantially reduced the glucosinolates content in sayur asin. After 3 days of fermentation the sinigrin content was reduced by 95% as compared to that in the raw vegetable. The indole GLSs 4-methoxy-glucobrassicin and neo-glucobrassicin concentration decreased to 80-90% of the fresh materials. However, the decreasing mechanisms as well as factors contributing to the decrease of the glucosinolates could not be explained yet.